Linking Emotions and Ergonomics : The Case of Spectacle Design for Teenagers - Kee, Man Chuah; Chee , Siong Teh (Fifth International Cyberspace Conference on Ergonomics, 2008)
One of the major effects of globalization on consumer market is that consumers are able to gain access to vast variety of products across the globe more easily than before thanks to the rapid development of the Internet. This has made consumers to be more selective and demanding than ever. In meeting such demands, product designers will have to use various means to increase consumer satisfaction by designing products that appeal to the intended target group. This paper describes the use of Kansei Engineering methods as one of the means to create desirable products. In particular, it presents the preliminary stage of an on-going research and development work done on a design support system, which aims to aid the design selection of spectacles. With the aid of three-dimensional graphics, subjective evaluations using Kansei Engineering methods are conducted to examine the relationship between users’ assessments and design elements.